2016
DOI: 10.1017/aee.2016.20
|View full text |Cite
|
Sign up to set email alerts
|

Hopes and Prospects for the Sustainability Cross-Curriculum Priority: Provocations From a State-Wide Case Study

Abstract: This article draws on research data from a state-wide case study, intertwined with three key moments that occurred in late 2014, to critically engage with the hopes and prospects of the Sustainability Cross-Curriculum Priority (CCP) in Australian schools. These key moments — theIPCC 5th Assessment Synthesis Report(Intergovernmental Panel on Climate Change, 2014), the conclusion of the United Nations Decade of Education for Sustainable Development, 2005–2014 (UNDESD), and the release of the Australian Governmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Environmental learnings should therefore emerge in multiple disciplinary contexts, enabling the development of a cumulative, coherent, and usable understanding of our environmental concerns. Hill and Dyment (2016) join our scepticism as to the future implementation successes of the CCPs. Hill and Dyment found that teachers report not to have the time, content knowledge or interest to incorporate Sustainability into their general planning, resulting in this particular CCP not living up to its title of being a priority (Casinader & Kidman, 2018).…”
Section: The Curriculum As An Enabler or Disablermentioning
confidence: 97%
“…Environmental learnings should therefore emerge in multiple disciplinary contexts, enabling the development of a cumulative, coherent, and usable understanding of our environmental concerns. Hill and Dyment (2016) join our scepticism as to the future implementation successes of the CCPs. Hill and Dyment found that teachers report not to have the time, content knowledge or interest to incorporate Sustainability into their general planning, resulting in this particular CCP not living up to its title of being a priority (Casinader & Kidman, 2018).…”
Section: The Curriculum As An Enabler or Disablermentioning
confidence: 97%
“…It should explicitly emerge in these multiple disciplinary contexts, thus enabling the student to develop a cumulative, coherent, and usable understanding of the priority. Hill and Dyment (2016) join our scepticism as to the future implementation successes of the CCPs. Hill and Dyment ask ‘Is the very concept of a cross-curriculum priority oxymoronic?…”
Section: Educating For Sustainabilitymentioning
confidence: 99%
“…However, this requirement for sustainability education is not as explicit as some writers would have liked, for they have argued that while ‘the Australian Curriculum neither prescribes nor particularly encourages the processes and understandings underpinning commitment to sustainability, it allows ample opportunity for teachers to engage with EfS and to incorporate sustainability as a core priority in the primary curriculum’ (Kennelly, Taylor, & Serow, 2011, p. 211, emphasis in original). Although this current article does not aim to provide an in-depth content analysis of the Australian Curriculum in relation to sustainability-focused content, we do, however, provide a surface overview, as called for by Hill and Dyment (2016).…”
Section: Educating For Sustainabilitymentioning
confidence: 99%
“…To gain buy in, green initiatives must be practical, actionable, and promoted by forward-thinking management. Hill and Dyment (2016) described the challenges educators faced in introducing sustainability concepts in the classroom. This 2016 study reported two vital challenges teachers noted as rational for not including detailed sustainability topics in the classroom: the instructors limited understanding of embedding sustainability concepts into the curriculum (Hill & Dyment, 2016).…”
Section: Taking Action: Csr In Corporationsmentioning
confidence: 99%
“…Hill and Dyment (2016) described the challenges educators faced in introducing sustainability concepts in the classroom. This 2016 study reported two vital challenges teachers noted as rational for not including detailed sustainability topics in the classroom: the instructors limited understanding of embedding sustainability concepts into the curriculum (Hill & Dyment, 2016). While there is a need to educate our youth, educators themselves may not be prepared to introduce sustainability topics.…”
Section: Taking Action: Csr In Corporationsmentioning
confidence: 99%